2015
DOI: 10.1515/acgeo-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Seismic Site Coefficient and Seismic Microzonation of Imphal City, India, Using the Probabilistic Approach

Abstract: A b s t r a c t Seismic site coefficients (F s ) for Imphal city have been estimated based on 700 synthetically generated earthquake time histories through stochastic finite fault method, considering various combinations of magnitudes and fault distances that may affect Imphal city. Seismic hazard curves and Uniform Hazard Response Spectra (UHRS) are presented for Imphal city. F s have been estimated based on site response analyses through SHAKE-91 for a period range of engineering interest (PGA to 3.0 s), for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The estimation method in determining the seismic site coefficient has been carried out by [9]. It can be categorized as an estimation method because the exciting force used in bedrock is a synthetically generated earthquake time theory through stochastic finite-fault method.…”
Section: Of May 27th 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…The estimation method in determining the seismic site coefficient has been carried out by [9]. It can be categorized as an estimation method because the exciting force used in bedrock is a synthetically generated earthquake time theory through stochastic finite-fault method.…”
Section: Of May 27th 2006mentioning
confidence: 99%
“…The results showed that the Fa and Fv site coefficient obtained from the study was relatively close to the Fa and Fv written in the Code. The main aim of this study is to develop the site coefficient maps at Yogyakarta Special Province (YSP) by applying the combination of the method that has been used by [9] and [10]. In the meantime, the shear wave velocity data in YSP is not yet available therefore the VS30 data published by USGS has been used.…”
Section: Of May 27th 2006mentioning
confidence: 99%